Address at the opening of the Twenty-eighth Session - Monsell, William (Statistical and Social Inquiry Society of Ireland, 1874)
I cannot commence this address without first thanking you for having elected me your President. The names of the distinguished men who have held this office cast a lustre around it; and I count it no mean honour to be allowed to occupy this chair. It has been usual to commence each new session with a review of the legislation of the year; and to point out errors and defects in existing laws with a view to their amendment. These suggestions have produced papers of conspicuous ability, which have been read and discussed at your meetings. I propose, with your permission, to take on this occasion a different course. The effect of laws depend much on the dispositions of the people for whom they are made. The seed sown by the legislator, however good it may be, produces scanty fruit if the soil that receives is impregnated with distrust or discontent. This, then, is the question I ask you to consider with me to-night ?not whether the statute book contains any unwise laws?not whether there are unredressed grievances to be found in our social system?but whether Ireland suffers from wrongs and grievances not existing in the rest of the United Kingdom.
Read before the Society, 24 November 1874
Keywords: Legal system in Nineteenth century Ireland; Irish oppression; Inequality in law; 314.15